Laparoscopy superseding open appendectomy: a prospective view - Deshpande, Amol; Khade, Shardul (International Surgery Journal, 2020)
Background: Appendicitis is the most common surgical disease with appendectomy being the traditional treatment of choice. Different operative procedures exist for appendectomy. The objectives of the study were to compare the efficiency of laparoscopic versus open appendectomy and to compare post-operative complications between laparoscopic and open appendectomy. Methods: This is a longitudinal study done from January 2018 till January 2020 in a tertiary care hospital of central India. A total of 400 operative patients were randomly selected and analysed with acute appendicitis (AA) as diagnosis. Sample size was randomized into two groups. Data was analysed with of open Epi version 2.3 and p value <0.05 was considered significant. Results: Most common symptom was pain in right iliac fossa (94.63%). 18.18% had perforation while 26.38% had inflamed appendix. Histopathological assessment showed that 8.3% and 2.87% had suppurative and gangrenous appendicitis respectively. 23.82% of the open cases reported with surgical site infection (SSI). No SSI were reported in the laparoscopic group. Post-op duration for open and laparoscopic appendectomy was 4.91±0.86 and 2.98±0.76 (p value=0.04150) and was found to be statistically significant. Conclusions: Open appendectomy is considered safe and effective but associated with complications such as ileus, intestinal obstruction, and wound sepsis. Laparoscopic appendectomy with high accuracy and low complication rate has emerged as the modus operandi and has superseded the open approach for treatment of AA.